2004
DOI: 10.1111/j.1467-9817.2004.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between language teachers' attitudes and the state‐trait anxiety of adolescents with dyslexia

Abstract: The aim of the present study was to investigate the role anxiety plays in the lives of adolescents with dyslexia by including a school perspective with special emphasis on the role of the teacher. The state‐trait anxiety of 68 adolescents with dyslexia and their language teachers' attitudes towards them were compared with an equal number of matched controls. State‐trait anxiety was measured by the Greek adaptation (Psychountaki, 1995) of Spielberger's State‐Trait Anxiety Inventory for Children (Spielberger, Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 55 publications
(55 reference statements)
4
17
0
Order By: Relevance
“…The STPI is designed to measure both A-State and A-Trait. In order to focus on reading and academic achievement the instructions for the A-State scale were adjusted (see Sagi-Nakav & Shany, 2011;Tsovili, 2004). The participant's response to the state items measures their feelings at such time by asking each participant to rate on a four-point scale from 1 (not at all) to 4 (very much).…”
Section: Behavioural Measuresmentioning
confidence: 99%
See 4 more Smart Citations
“…The STPI is designed to measure both A-State and A-Trait. In order to focus on reading and academic achievement the instructions for the A-State scale were adjusted (see Sagi-Nakav & Shany, 2011;Tsovili, 2004). The participant's response to the state items measures their feelings at such time by asking each participant to rate on a four-point scale from 1 (not at all) to 4 (very much).…”
Section: Behavioural Measuresmentioning
confidence: 99%
“…Adults with RD manifest difficulties with fluent and/or accurate word recognition and poor spelling and decoding performance (Lyon, Shaywitz, & Shaywitz, 2003). Some studies have found that individuals with RD are more likely to experience stress, worry and anxiety when placed in a situation demanding literacy ability (Carroll & Iles, 2006;Maughan & Carroll, 2006;Tsovili, 2004) and tend to read only when they have to (Stanovich, 1986). Anxiety caused by reading can influence other performances.…”
Section: Potential Links Between Anxiety and Reading Disabilitymentioning
confidence: 99%
See 3 more Smart Citations